An Analysis of Mass Communication in the Pandemic (In the Example of Coca Cola Ads) - Ebru Çitil (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
The pandemic called Covid 19, which emerged in the last period of 2019, turned into a chaos that affected the whole world physically and psychologically. The pandemic period caused people's habits and communication styles to change. It has become a way of life for people to be unable to leave their homes due to restrictions. This situation has also caused a change in the way global brands reach consumers and the content of their advertising messages. In this study, two commercials prepared by the Coca Cola brand during the period when the effects of the pandemic were felt intensely and the effects of the pandemic were relatively alleviated were analyzed by semiotic analysis method. In this research, it is aimed to reveal how and for what purpose an international brand gives messages on a global scale in its advertisements, which intercultural codes it brings to the fore, to reveal the messages behind the visible messages and which elements in mass communication and for what purpose they are effective on people. The findings of the analysis carried out in the context of signifier-signified, denotation-connotation in the research overlap with the theoretical foundations of semiotics.